WEBSITE ASSOCIATION BUSINESS DEVELOPMENT SERVICE INDONESIA WILAYAH KALIMANTAN TENGAH - Sherly Christina; Abertun Sagit Sahay; Beni Trijoko (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
Association Business Development Service Indonesia (ABDSI) is a service provider forBusiness Development Cooperatives and Small Micro and Medium Entrepreneurs (SMMEs).ABDSI Central Kalimantan needs a media to give information to SMME that spread in CentralKalimantan.Website for ABDSI was built based on Web 2.0 technology. The methodology to model thiswebsite UML-based Web Engineering (UWE) that has four steps , each step of the methodology isstructured, visualized, and documented clearly. The softwares that is used to develop this websiteare PHP, MySQL database, Adobe Dreamweaver CS5, Javascript, Jquery. The Blackbox Testingwas used to test the functionality.The result of blackbox testing shows that this website can be used as a media to inform andpromote ABDSI profile, activities, and training that can be shared to the SMMEs and the Society.For the future works the website can be improved to facilitate the communication between ABDSIand SMMEs with more interactive medias such as video call, online chat and SMS gateway.